Summary of Canadian Guidelines for the Initial Management of Community-Acquired Pneumonia: An Evidence-Based Update by the Canadian Infectious Disease Society and the Canadian Thoracic Society - Lionel A Mandell; Thomas J Marrie; Ronald F Grossman; Anthony W Chow; Robert H Hyland; Canadian CAP Working Group (Canadian Journal of Infectious Diseases)
Community-acquired pneumonia (CAP) is a serious illness with a significant impact on individual patients and society as a whole. Over the past several years, there have been significant advances in the knowledge and understanding of the etiology of the disease, and an appreciation of problems such as mixed infections and increasing antimicrobial resistance. The development of additional fluoroquinolone agents with enhanced activity against Streptococcus pneumoniae has been important as well. It was decided that the time had come to update and modify the previous CAP guidelines, which were published in 1993. The current guidelines represent a joint effort by the Canadian Infectious Diseases Society and the Canadian Thoracic Society, and they address the etiology, diagnosis and initial management of CAP. The diagnostic section is based on the site of care, and the treatment section is organized according to whether one is dealing with outpatients, inpatients or nursing home patients.